Caffeine Tolerance in the Fly Drosophila Melanogaster - Prevot, Luca B. (My University, 2006)
Responding to cues that precede and signal important biological events (anticipatory learning) may have important fitness consequences. Anticipatory learned responses have high adaptive value when intervene in the regulation of physiological states, and one widely studied example of learning-mediated homeostatic regulation is tolerance to drugs. Physiological responses that offset drugs' effects, like many other autonomic responses, can become classically conditioned to environmental cues that are repeatedly paired with drug intake. Caffeine is a widely used model substance for studying mechanisms related to drug intake, tolerance and addiction. In this report I provided evidence of tolerance development to some caffeine effects in the fruit fly, Drosophila melanogaster, which is a novel finding. I then showed that the tolerance is mediated by classical conditioning. A surprising result was that tolerance was completely and not, as more generally found, only partially mediated by conditioning. Together with other drugs, caffeine appears to be a promising substance to be used in the fly to study the pharmacology of substances with addictive potential. Also, these results indicate that this system may be an optimal model for the study of the adaptive value of learning in an insect species.
Title: Caffeine Tolerance in the Fly Drosophila Melanogaster, Author: Luca B. Prevot, Location: Thode